-7(6+d)=-70

Simple and best practice solution for -7(6+d)=-70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6+d)=-70 equation:



-7(6+d)=-70
We move all terms to the left:
-7(6+d)-(-70)=0
We add all the numbers together, and all the variables
-7(d+6)-(-70)=0
We add all the numbers together, and all the variables
-7(d+6)+70=0
We multiply parentheses
-7d-42+70=0
We add all the numbers together, and all the variables
-7d+28=0
We move all terms containing d to the left, all other terms to the right
-7d=-28
d=-28/-7
d=+4

See similar equations:

| 3x-5=2x-4+ | | 3x+6+1=8 | | 18=6+2d | | -0.4=g-4.5 | | 3x-5=2x-40 | | 5m÷3=4÷9 | | -3g=2 | | m3+ 9= 13 | | b/17-7b/17=48/17 | | 11/12x=560 | | 11/12x=569 | | X+.07x=4.78 | | 5x-20=10x-15 | | 7x+5x+x=180 | | 2=7+r8 | | |20-7x|=8 | | 3x-2(3x-12)=60 | | (x+1)(x-1)(x-4)(x+4)(x-5)=0 | | 4(2k-8)=k+1 | | 1+8k=-5+7k | | 8x+15x=115 | | -25=-312+x | | 3c-38=4c-55 | | Y+1=(3x-4) | | m+1013=2 | | 6x–2+3x=–2x+6–5x | | 25=(-8)+9(x+3) | | -x-16=2x-11x | | 5d+10-4=13.5 | | v+12=3 | | |3x+5|=8 | | 5n–12=–3n+4 |

Equations solver categories